Criminological Study of Personality-Based Crimes in Cyberspace; from Typology to Policy Strategies - Ehsan Salimi Ghalehei; Sepideh Bouzari; Parviz Dehghani (International Journal of Web Research)
Harassment-based crimes targeting the spiritual integrity of victims are among the most numerous and varied offenses in cyberspace, ,which can be categorized under the general title of harassment in cyberspace. According to the unique properties and meta-variables of information and communication technology, the rate of harassment crime in cyberspace is more than that of real space. This study, a descriptive-analytical meta-analysis, aims to critically examine personality-based crimes and harassment in cyberspace. It seeks to identify the types of crimes, the characteristics of the victims, and the criminal profiles of the offenders. Findings reveal that these crimes are predominantly perpetrated by young men with diverse motivations, particularly of a sexual nature, targeting teenage girls. Based on these findings, it is recommended that legislators adopt a differential and aggravated approach to criminalize harassment against women and children. Additionally, addressing the role and needs of victims in crime responses is crucial. Furthermore, identifying and criminalizing emerging personality-based behaviors, balancing crime platform filtering, adopting participatory criminal policies involving non-governmental organizations, empowering users with preventive oversight and technical measures, and enhancing media literacy and cultural norm-setting are essential strategies for combating personality-based crimes.